Arabic Curriculum for Elementary School in Indonesia/منهج تعليم اللغة العربيّة للمدرسة الإبتدائية في إندونيسيا - Hidayah, Nur (Nurul Jadid University, 2017)
The aim of this research is to know the concept of curriculum for teaching Arabic language and its application process. It also goes to know the four elements of the curriculum (objectives, content, method, method and evaluation) in primary school in Indonesia.يهدف هذا البحث إلى معرفة مفهوم المنهج لتعليم اللغة العربيّة وعملية تطبيقه كما أنه يذهب إلى معرفة عناصر المنهج الأربعة (وهي الأهداف والمحتوى والطريقة ووسيلتها والتقويم) في المدرسة الإبتدائية بإندونيسيا.